Society under Sustainable Developments Prospective in District of Elbasan, Albania - Duka, Evisa (Mediterranean Journal of Social Sciences, 2012)
The purpose of this proposed session is to introduce the status of sustainable development in my country Albania,bringing in attention sustainable development and society in a very symbolic district of the Country, the Elbasan district. Underthe Global Millenniums Goals, the society across the world is ambitiously exercising principles of sustainable development,linking economy, society and environment toward a better wellbeing for future generations. Sustainable development principlesrequire societal actions beyond borders of states, political and economy sectors, as well as of the generations and societaldiversities.What is the Albanian contribution with regards to the Earth Summit Challenges, while it is fully integrating in theregional and global processes under the freedoms of market economy? Through my paper I will introduce the status ofsustainable development in my country Albania, bringing in attention sustainable development and society in a very symbolicdistrict of the Country, the Elbasan district, pointing out local societies both as contributors and beneficiaries in the process. I willpresent district natural and human resources under the sustainable prospective, while a lot of work needs to be done in order toprevent the very critical environmental condition along the city or periphery due to former metallurgy activity in the district. Therole of society is indispensable in the process, while bottom up initiatives must push local and central governments to design andimplement budgets fostering a sustainable development.